MORPHOMETRIC ASSESSMENT OF STRUCTURAL CHANGES IN THE DUODENAL WALL OF RATS CAUSED BY SKIN BURN INJURY UNDER CONDITIONS OF EXPERIMENTAL DIABETES - Tymoshenko, I.O.; Cherkasov, E.V.; Shepitko, K.V. (World of Medicine and Biology, 2020)
This work is devoted to the morphometric assesment of structural changes in the duodenal wall of rats with skin burn injury under conditions of experimental diabetes mellitus. The control group included 21 intact animals without any signs of somatic pathology, experimental group I consisted of 21 rats with experimental skin burn injury, experimental group II consisted of 21 rats without skin burns but with experimentally simulated diabetes mellitus, and experimental group III consisted of 21 rats with both skin burn injury and experimentally simulated diabetes mellitus. The following morphometric parameters have been studied: mucosal thickness, villi height and thickness, crypt depth and width, thickness of lamina muscularis of mucosa, submucosa thickness, muscular layer thickness, serosa thickness, height of the epitheliocytes in the middle part of the villi, mitotic index of columnar epitheliocytes. The obtained data confirm the progredient course of changes characteristic of diabetic enteropathy, which gradually worsen after 7, 14 and 21 days of the experiment.
Keywords: skin burn injury; streptozotocin-induced diabetes mellitus; duodenal wall; morphometric assessment